Conference report: OAI7 — Raising the Bar for Current Developments in Scholarly Communication, A Personal View - Ayris, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2011)
The purpose of this paper is to give an overview of the presentations and sessions at the OAI7 Workshop in the University of Geneva, 22–24 June 2011. The theme of the Workshop was, as always, Innovations in Scholarly Communication. The Workshop was attended by a record number of 267 delegates. Thirty-four posters were submitted for the Poster session. There were 6 tutorials, 6 plenary sessions and 6 technical sessions. The paper identifies some of the highlights of the Workshop and updates two previous review articles by Professor Raf Dekeyser and the author on the history of the OAI meetings.